Identification of Rice Blast Loss-of-Function Mutant Alleles in the Wheat Genome as a New Strategy for Wheat Blast Resistance Breeding - Guo, Huijun; Du, Qidi; Xie, Yongdun; Xiong, Hongchun; Zhao, Linshu; Gu, Jiayu; Zhao, Shirong; Song, Xiyun; Islam, Tofazzal; Liu, Luxiang (Frontiers in Genetics, 2021)
Blast is caused by the host-specific lineages of the fungus Magnaporthe oryzae and is the most important destructive disease in major crop plants, including rice and wheat. The first wheat blast outbreak that occurred in Bangladesh in 2016 and the recent epidemic in Zambia were caused by the Magnaporthe oryzae Triticum (MoT) pathotype, a fungal lineage belonging to Magnaporthe oryzae. Although a few reported wheat cultivars show modest resistance to MoT, the patterns of genetic variation and diversity of this pathotype make it crucial to identify additional lines of resistant wheat germplasm. Nearly 40 rice blast resistant and susceptible genes have so far been cloned. Here, we used BLAST analysis to locate two rice blast susceptible genes in the wheat reference genome, bsr-d1 and bsr-k1, and identified 6 identical homologous genes located on subgenomes A, B and D. We uncovered a total of 171 SNPs in an EMS (ethyl methane sulphonate)-induced population, with mutation densities ranging from 1/1107.1 kb to 1/230.7 kb through TILLING (Targeting Induced Local Lesions IN Genomes) by sequencing. These included 81 SNPs located in exonic and promoter regions, and 13 coding alleles that are predicted to have severe effects on protein function, including 2 premature mutants that might affect wheat blast resistance. The loss-of-function alleles identified in this study provide insights into new wheat blast resistant lines, which represents a valuable breeding resource.